The politics of implementation: The role of traditional authorities in delivering social policies to poor people in Kenya. (August 2021) - Rohregger, Barbara; Bender, Katja; Kinuthia, Bethuel Kinyanjui; Schüring, Esther; Ikua, Grace; Pouw, Nicky
The article contributes to understanding the political economy of implementation of social protection programmes at local level. Current debates are dominated by technocratic arguments, emphasizing the lack of financial resources, technology or skills as major barriers for effective implementation. Describing how chiefs, assistant-chiefs and community elders are routinely at the centre stage of core implementation processes, including targeting, enrolment, delivery, monitoring, awareness and information, data collection or grievance and redress, this study on Kenya argues for the need to look more closely into the local political economy as an important mediating arena for implementing social policies. Implementation is heavily contingent upon the local social, political and institutional context that influences and shapes its outcomes. These processes are ambivalent involving multiple forms of interactions between 'formal' and 'informal' institutional structures, which may support initial policy objectives or induce policy outcomes substantially diverging from intended policy objectives.